Highly Oxidizing Aqueous Environments on Early Mars Inferred From Scavenging Pattern of Trace Metals on Manganese Oxides. Issue 5 (16th May 2019) - Noda, Natsumi; Imamura, Shoko; Sekine, Yasuhito; Kurisu, Minako; Fukushi, Keisuke; Terada, Naoki; Uesugi, Soichiro; Numako, Chiya; Takahashi, Yoshio; Hartmann, Jens
Abstract: The Curiosity and Opportunity rovers have found depositions of manganese (Mn) (hydr)oxides within the veins of the sedimentary rocks at Gale and Endeavour craters. Since Mn is a redox sensitive element, revealing the chemical form of the Mn (hydr)oxide provides unique information on the redox state of the near‐surface/groundwater at the time of deposition. Here we report results of laboratory experiments that investigated scavenging patterns of trace metals (zinc, nickel, and chromium) on different Mn (hydr)oxides in order to constrain the chemical form of the Mn precipitates found on Mars. Our results show manganese dioxide (MnO2 ) scavenges zinc and nickel effectively but not for chromium. The agreement of this scavenging pattern with the observations strongly suggests that the Mn (hydr)oxides found on Mars are highly likely to be MnO2 . To form MnO2, oxidizing aqueous environments are required (e.g., Eh > 0.5 V at pH ~ 8). The candidates of the oxidant include molecular oxygen, ozone, nitrates, and perchlorate acids; all of which are considered to be produced by photochemical processes. The presence of MnO2 veins in sediments suggests that such atmospheric high‐Eh oxidants may have been supplied to the subsurface, possibly through hydrological cycles activated by transient warming. Plain Language Summary: Early Mars is believed to have possessed an abundance of liquid water on its surface. The Mars rover Curiosity has found both complex organic matter and bio‐essential elements within the lake deposits at Gale crater. To further understand habitability on early Mars, knowledge of the redox states of the aqueous environments is essential because redox disequilibria in environments provide chemical energy to chemoautotrophic life. A key to constraining the redox states is the enrichment of "redox sensitive elements" within sediments. Manganese (Mn) is a redox‐sensitive element, changing its chemical form depending on the redox states. Curiosity and Mars Exploration Rover Opportunity have found Mn enrichments within the veins of ancient sediments on Mars; however, their chemical forms are poorly constrained. Here we constrain the chemical form of the Mn enrichments based on precipitation experiments. Our results suggest that the Mn enrichments on Mars were caused by deposition of MnO2, which requires highly oxidizing conditions in the aqueous environment at the time of deposition. The candidates of the oxidant include molecular oxygen, ozone, perchlorates, and nitrates. We suggest that these oxidants formed in the atmosphere and may have been supplied into reducing groundwater via hydrological cycles on early Mars. Key Points: Scavenging pattern of trace metals on Mn (hydr)oxides is investigated by precipitation experiments The scavenging pattern for MnO2 is consistent with the measurements of trace metals within Mn‐rich veins found on Mars To form MnO2, high‐Eh oxidants formed in the atmosphere need to be supplied to groundwater on early Mars